2017
DOI: 10.1182/bloodadvances.2017009795
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group A transferases catalyze the biosynthesis of FORS blood group FORS1 antigen upon deletion of exon 3 or 4

Abstract: Key Points• ABO blood group A transferases possess intrinsic FS activity upon deletion of exon 3 or 4 of A transferase messenger RNAs.• Cointroduction of exon 3 or 4 deletion and GlyGlyAla substitution synergistically confers human A transferases with strong FS activity. (B3GALNT1) cells, and cell-surface expression of FORS1 was immunologically monitored. To our surprise, the deletion of exon 3 or 4, but not of exon 2 or 5, of human AT transcripts bestowed moderate FS activity, indicating that the A allele is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 61 publications
(66 reference statements)
3
19
0
Order By: Relevance
“…The current study showed that this construct also exhibited weak FS activity and that the Met69Thr substitution was responsible for the FS activity. Together with our previous finding that the GlyGlyAla substitution at codons 266 to 268 of human AT and the deletion of exon 3 or 4 of AT mRNAs also endowed FS activity, 14,16 it is evident that multiple molecular mechanisms exist allowing the crosstalk between ABO and FORS systems. The fact that FS activity was enhanced by the cointroduction of GlyGlyAla tripeptide and Met69Thr substitutions suggests 2 different synergistic mechanisms.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…The current study showed that this construct also exhibited weak FS activity and that the Met69Thr substitution was responsible for the FS activity. Together with our previous finding that the GlyGlyAla substitution at codons 266 to 268 of human AT and the deletion of exon 3 or 4 of AT mRNAs also endowed FS activity, 14,16 it is evident that multiple molecular mechanisms exist allowing the crosstalk between ABO and FORS systems. The fact that FS activity was enhanced by the cointroduction of GlyGlyAla tripeptide and Met69Thr substitutions suggests 2 different synergistic mechanisms.…”
Section: Discussionsupporting
confidence: 60%
“…Human AT and derivatives having GlyGlyAla or MetGlyAla tripeptide, mouse cis-AB transferase, and mouse FS constructs H_ABO-A, H_ABO-A(GlyGlyAla), H_ABO-A(MetGlyAla), M_ABO-AB, and M_GBGT1, respectively, were prepared in the pSG5 eukaryotic expression plasmid vector as previously described. 7,14,16 Additional amino acid substitution constructs were prepared by in vitro mutagenesis, employing the 2-round primermediated polymerase chain reaction strategy using primers with nucleotide substitutions. 7,16 DNA transfection…”
Section: Preparation Of Amino Acid Substitution Constructs By In Vitrmentioning
confidence: 99%
See 3 more Smart Citations